Gizi Seimbang Sebagai Bentuk Melindungi Diri Dari Risiko Kejadian Beban Gizi Ganda Siswa Sdn 1 Benten Kec. Baranti Kab. Sidrap - Nursiah, Andi; Idris, Idris; Srifitayani, Nur Rahma; Syahrir, Sri Sukmawaty; Nurasbon, Nurasbon; Irdan, Irdan; Utami, Dia Rejeki; Ernawati, Ernawati; Nurhidaya, Nurhidaya (Barongko: Jurnal Ilmu Kesehatan, 2025)
Malnutrition is a nutritional imbalance in the body. This imbalance is caused by nutritional intake that does not match a person's nutritional needs. The purpose of this study was to determine the decrease in the incidence of double nutritional burden in students of SDN 1 Benteng, Baranti District, Sidrap Regency. This research method is a quantitative study with a case control approach. The results of the study showed that children who often consume excess nutritional events are almost the same as children with normal nutritional status, meaning there is no relationship between the frequency of consumption and the incidence of excess nutrition in children. The conclusion is that malnutrition does not only occur when a toddler is born, but because the toddler's mother already has a history of malnutrition as a result of the low nutritional intake consumed by the toddler's mother. Mothers with low energy intake are called Mothers with Chronic Energy Deficiency.